How far do we still need to go? A survey on knowledge, attitudes, practice related to antimicrobial stewardship regulations among Chinese doctors in 2012 and 2016. Issue 6 (5th June 2019) - Xia, Ruyu; Hu, Xiaoyang; Willcox, Merlin; Li, Xinxue; Li, Yuxiu; Wang, Jian; Li, Xun; Moore, Michael; Liu, Jianping; Fei, Yutong
Abstract : Objectives: To explore doctors' knowledge, willingness, concerns and the countermeasures to the most stringent antimicrobial stewardship regulations of China which implemented in August 2012. Design: Cross-sectional survey. A pretested 32-point structured questionnaire was distributed to doctors by sending a web link via the mobile phone application WeChat through snowball sampling methods and email groups of medical academic societies. Setting: China. Participants: Doctors. Primary and secondary outcome measures: The questionnaire inquired about the doctors' experiences, knowledge, willingness, concerns and the countermeasures to the stewardship policies. Results: Total of persons in the groups was 19 791, among them 1194 submitted the answers, within them, 807 were doctors. Doctors had a mean age of 39.0 years. The majority (78.9% in 2012, 89.1% in 2016) reported that they were willing or very willing to accept the regulations. Almost all respondents (93.2%) felt the stewardship regulations had the potential to adversely affect the prognosis of patients who would have been prescribed antimicrobials before they were implemented, and >65% (65.7% in 2012, 66.9% in 2016) of doctors were often or always concerned about the prognosis of these patients. In 2012, 32% of doctors prescribed restricted antimicrobials or suggested patient self-medication with restricted antimicrobials to address doctors' concerns, and this number decreased to 22.6% in 2016. Although compulsory antimicrobial stewardship training was frequent, less than half of respondents (46.8%) responded correctly to all three knowledge questions. Conclusion: Antimicrobial stewardship regulations had some positive effect on rational antimicrobial use. Willingness and practice of doctors towards the regulations improved from 2012 to 2016. Knowledge about rational antimicrobial use was still lacking. Doctors found ways of accessing restricted antibiotics to address their concerns about the prognosis of patients, which undermined the implementation of the stewardship regulations.